Subaltern urbanism as a way of life: Redefining and (re)imagining postcolonial urbanity in Bulawayo, Zimbabwe - Talent Moyo (Taylor and Francis Group, 2023)
The paper contends that subaltern urbanism is a way of life in the context of contemporary Zimbabwe. Through ethnography conducted in Bulawayo, Zimbabwe, between February 2019 and May 2019, the paper extends the concept of subaltern urbanism through presenting subaltern urbanism as a way of life that encapsulates individuality and urban governance. The paper argues that subaltern urbanism is scripted by individuals positioned at the bottom of the social ladder and urban governing institutions. The paper maintains the view that subaltern urbanism as a way of life denotes redefinition and (re)imagining contemporary post-colonial urbanity. Finally, the paper proposes the notion that the author labels as “subalternization of the city” by urban governing institutions and suggests new ways of understanding urbanism in Africa.